2014
DOI: 10.1038/bmt.2013.228
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of distress in patients after allogeneic hematopoietic SCT: Fear of progression is associated with a younger age

Abstract: Little is known about the psychological burden patients are left with after successful allogeneic hematopoietic SCT (HSCT). With the main focus on physical condition and common transplant complications, psychological symptoms often remain neglected in daily practice. To assess the prevalence of distress in patients who have undergone allogeneic HSCT, we conducted a cross-sectional pilot study in 50 consecutive patients from our outpatient transplant clinic using standardized questionnaires. Distress was catego… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 36 publications
5
32
1
1
Order By: Relevance
“…In particular, some authors showed that concerns for the future welfare of the children, responding to children's needs and grief related to potential loss of opportunities to engage in the children's upbringing were reported as major concerns. 6,30 The risk for high FCR through subclinical anxiety and depressive symptoms before the beginning of the therapy shows similarity to the concept of subsyndromal symptomatic depression, which has been defined as minimal depressive symptoms beneath the diagnostic threshold for minor, dysthymic or major depressive disorders. 31,32 Subsyndromal symptomatic depression is very commonly observed in patients with unipolar major depressive disorder 33 and is an integral component of the symptomatic course of illness.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, some authors showed that concerns for the future welfare of the children, responding to children's needs and grief related to potential loss of opportunities to engage in the children's upbringing were reported as major concerns. 6,30 The risk for high FCR through subclinical anxiety and depressive symptoms before the beginning of the therapy shows similarity to the concept of subsyndromal symptomatic depression, which has been defined as minimal depressive symptoms beneath the diagnostic threshold for minor, dysthymic or major depressive disorders. 31,32 Subsyndromal symptomatic depression is very commonly observed in patients with unipolar major depressive disorder 33 and is an integral component of the symptomatic course of illness.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, S.Sarkar et al (2014) note that often a situation of transplantation associated with fear of cancer recurrence (FCR) of BD, while being married (b = 2.76, P = 0.026), female gender (b = 4.45, P <0.001) and depression (b = 4.44, P <0.001) were significantly associated with FCR at baseline [100] . At the same time J.Hefner et al (2014) demonstrate the high prevalence of distress in patients who have undergone allogeneic HSCT and associate fear of progression with a younger age [101] . C. Meyers et al (1994) [65] studied psychogenic disorders in BMT in a situation of isolation.…”
Section: Adjustment Disordersmentioning
confidence: 99%
“…im Fall schwerer komorbider Depressivität [18]. Psychische Belastungen nach einer HSCT sind ebenfalls häufig und können noch Jahre nach der Transplantation von Bedeutung sein [5,11,18,19].…”
Section: Introductionunclassified